The odyssey - Konchalovsky, Andrei; Lovell, Dyson; Hallmark Entertainment; American Zoetrope (Firm) (Los Angeles, CA : Hallmark Home Entertainment, 1997)
Aided by the goddess Athena, warrior-king Odysseus braves the terrors and temptations of a fantastic array of creatures as his return from the Trojan War becomes a decade-long quest to reach his homeland and his faithful wife, Penelope
Title from title screen
Based on'The Odysses' by HOMER
Executive producer, Francis Ford Coppola, Fred Fuchs, Nicholas Meyer
Casts: Armand Assante, Greta Scacchi, Geradine Chaplin, Jeroen Krabbe, Chiristopher Lee, Irene Papas
Keywords: Adventure films; Feature films